FACTORS INFLUENCING CHILDHOOD VACCINATIONS - Bakhromjon M. Mamatqulov,; Gulkhayokhon K.Tolipova, (Central Asian Journal of Medicine, 2025)
Aim. Examination of parental perspectives on vaccination. Materials and Methods. Administering a survey to 980 parents residing in Tashkent and evaluating their results. Outcomes. The medical expertise of parents was examined. Increased medical education among parents correlates with greater responsibility in immunization practices. Conclusion. Enhancing parental access to information through media and social networks will result in a rise in vaccination rates.